Ecological and Health Risk Assessment of Metals in Organic and Conventional Peruvian Coffee from a Probabilistic Approach - Grobert A. Guadalupe; Ligia García; Segundo G. Chavez; Eva Doménech (Agronomy)
This study aims to understand the risks posed by metals in Peruvian coffee plantations to human health and environmental integrity, ensuring the protection of local communities and the ecosystems reliant on this agricultural activity. To assess the contamination levels, arsenic (As), cadmium (Cd), chromium (Cr), nickel (Ni), and lead (Pb) were surveyed in the soil, roots, and parchment coffee beans cultivated in Amazonas and San Martin regions, using both conventional and organic cultivation. Results showed that As was the metal with the highest concentration in soil (52.37 ± 21.16 mg/kg), roots (11.27 ± 2.3 mg/kg), and coffee beans (10.19 ± 1.69 mg/kg), followed by Cr in soil (22.36 ± 11.47 mg/kg) and roots (8.17 ± 3.85 mg/kg) and Pb in beans (0.7 ± 0.05 mg/kg). Cd was only detected in soil (1.70 ± 1.73 mg/kg). The bioaccumulation (BAF) findings suggest that roots and coffee beans have a low capacity to accumulate As, Cd, Ni, and Pb, but they have the potential capacity to accumulate Cr. The translocation factor (TF) indicated that all values were less than one, except for As from San Martin in conventional and organic cultivation. The geo-accumulation index (Igeo) showed that the soil was unpolluted for Cr, Ni, and Pb but was polluted to different extents for As and Cd. Similarly, the ecological risk (ER) pointed to a low risk for Cr, Ni, and Pb and values from low to considered risk for As and Cd depending on the region and cultivation system. Hazard index (adults: 1.68 × 10−3, children: 9.26 × 10−3) and cancer risk (adults: 1.84 × 10−7, children: 2.51 × 10−7) indicated a low risk for humans via ingestion, dermal contact, and inhalation.